High noon - Cooper, Gary, 1901-1961; Grace, Princess of Monaco, 1929-1982; Mitchell, Thomas, 1892-1962; Bridges, Lloyd; Jurado, Katy; Chaney, Lon, Jr., 1906-1973; Van Cleef, Lee, 1925-1989; Zinnemann, Fred, 1907-1997; Tiomkin, Dimitri, 1894-1979; Cunningham, John M. (United Artists, 1952)
A retiring sheriff feels a responsibility to an ungrateful town when challenged by a gunfighter.